E06 Neuroimaging In Huntington's Disease: On Brain Function, And On Brain Structure From Classical Approaches To Application Of Multivoxel Pattern Analysis. (17th September 2014) - Caetano, G; Lavrado, R; Júlio, F; Januário, C; Castelo-Branco, M
Abstract : Background: In Huntington's disease, structural and functional changes of the central nervous system affect primarily the basal ganglia and fronto-striatal circuitry, as demonstrated by large cohort studies. Aims: This project aims at detecting earliest functional/structural alterations in premanifest gene carriers (preHD). Here, we present year1 assessments with neuroimaging, including brain function, structure, and application of support vector machines. Methods: 18 controls, 14 preHD (far YEO), and 11 early-HD patients underwent MRI in a 3T Siemens Scanner. Acquisitions comprised two structural MRI scans, diffusion weighted imaging (60 directions, b = 1000), and fMRI study of oculomotor function. The latter included pro-saccades, anti-saccades, and 1-and-2 back memory-antisaccade. Additionally, oculomotor psychophysics were performed out-bore. Results: Early-HD participants have significant decreased volumes of basal ganglia structures, which correlated significantly with saccade express errors, and cortical thinning throughout an extended area. To preHD, thinning is identified once using less conservative thresholds. PreHD participant had decreased volume of the left caudate, and express and direction errors correlated with striatal volumes. On the other hand, when applying support vector machines to grey matter or fractional anisotropy (whole-brain, basal-ganglia ROIs), classification of HD versus pre-HD/controls attained accuracies above 80%, whereas preHD vs. Controls results were not significant. Finally, fMRI results showed robust difference between preHD and control group (RFX, cluster thresholded) for oculomotor tasks involving inhibitory components, in areas comprising caudate, ACC and pre-frontal cortex. Conclusions: HD patients had overall alterations whereas first HD-related detectable alterations might derive from neural dysfunction preceding and/or simultaneous to initial neural loss.